Amniotic fluid CD200 levels in pregnancies complicated by preterm prelabor rupture of the membranes. (September 2013) - Kacerovsky, Marian; Drahosova, Marcela; Krejsek, Jan; Musilova, Ivana; Hornychova, Helena; Matula, Vojtech; Simetka, Ondrej; Jacobsson, Bo; Andrys, Ctirad
Abstract Objective: To determine the amniotic fluid CD200 levels in uncomplicated pregnancies and in preterm prelabor rupture of the membranes (PPROM) according to microbial invasion of the amniotic cavity and histological chorioamnionitis and its association with neonatal outcomes. Methods: One hundred and fifty-nine women with singleton pregnancies were included in this study. Amniotic fluid was collected, and CD200 levels were determined using ELISA. Results: No difference was found in CD200 levels between women in the second trimester and women at term without labor. Women at term with labor had higher CD200 levels than women in the second trimester and women at term without labor. The presence of funisitis in PPROM pregnancies was associated with higher CD200 levels independent of gestational age (with funisitis: median 197.5 pg/mL versus without funisitis: median 61.0 pg/mL; p = 0.003). The need for tracheal intubation and the development of bronchopulmonary dysplasia were associated with higher CD200 levels. Conclusions: Amniotic fluid CD200 levels remained stable in advanced pregnancy and they were increased during parturition. Elevated CD200 levels in the presence of funisitis suggest the involvement of negative regulatory mechanisms of innate immunity. CD200 may play a role in the development of pulmonary aspects of neonatal morbidity.